Claiming parity between unequal partners: how African counterparts are framed in the externalisation of EU migration governance. Issue 3 (27th May 2019) - Strange, Michael; Oliveira Martins, Bruno
ABSTRACT: The externalisation of European Union migration governance disproportionately impacts states based on the African continent. Much of the analytical focus amongst existing research has been on the agency of the EU and its Member-states, identifying the asymmetric and postcolonial character of these policies, as well as highlighting that the imposition of European interests on African states risks undermining their own political stability. Yet, there is significant effort spent by actors on both sides of the Mediterranean on making African counterparts visible as an equal partner – an endeavour seen not just rhetorically within speeches, but also in the set-up of key institutional fora and their membership. The article approaches the framing processes involved to trace the legitimating basis of EU-Africa relations and the externalisation of EU migration policy to African states, highlighting how African political actors are positioned as participating in what is an EU-led process.